Hyperbaric Medicine - Balestra, Costantino; Kot, Jacek (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Hyperbaric oxygen is a known therapeutic agent, and treatments using this agent remain a matter of discussion and research. This Special Issue collection will add new knowledge and also offer some not so usual approaches to foster contemporary understanding and potential benefit for patients and scholars.